Prognostic value of extrahepatic metastasis on colon cancer with liver metastasis: a retrospective cohort study - Bai, Shuheng; Chen, Ling; Zhu, Guixian; Xuan, Wang; Hu, Fengyuan; Liu, Wanyi; Li, Wenyang; Lan, Ning; Chen, Min; Yan, Yanli; Li, Rong; Yang, Yiping; et al. (Frontiers in Oncology, 2023)
Introduction: The occurrence of metastasis is a threat to patients with colon cancer (CC), and the liver is the most common metastasis organ. However, the role of the extrahepatic organs in patients with liver metastasis (LM) has not been distinctly demonstrated. Therefore, this research aimed to explore the prognostic value of extrahepatic metastases (EHMs). Methods: In this retrospective study, a total of 13662 colon patients with LM between 2010 to 2015 were selected from the Surveillance, Epidemiology, and End Results database (SEER). Fine and Gray's analysis and K-M survival analysis were utilized to explore the impacts of the number of sites of EHMs and different sites of EHMs on prognosis. Finally, a prognostic nomogram model based on the number of sites of EHMs was constructed, and a string of validation methods was conducted, including concordance index (C-index), receiver operating characteristic curves (ROC), and decision curve analysis (DCA). Results: Patients without EHMs had better prognoses in cancer-specific survival (CSS) and overall survival (OS) than patients with EHMs (p<0.001). Varied EHM sites of patients had different characteristics of primary location site, grade, and histology. Cumulative incidence rates for CSS surpassed that for other causes in patients with 0, 1, 2, ≥3 EHMs, and the patients with more numbers of sites of EHMs revealed worse prognosis in CSS (p<0.001). However, patients with different EHM sites had a minor difference in cumulative incidence rates for CSS (p=0.106). Finally, a nomogram was constructed to predict the survival probability of patients with EHMs, which is based on the number of sites of EHMs and has been proven an excellent predictive ability. Conclusion: The number of sites of EHMs was a significant prognostic factor of CC patients with LM. However, the sites of EHMs showed limited impact on survival. Furthermore, a nomogram based on the number of sites of EHMs was constructed to predict the OS of patients with EHMs accurately.